Maltreatment, the Oxytocin Receptor Gene, and Conduct Problems Among Male and Female Teenagers - Andreou, Dimitrios; Comasco, Erika; Åslund, Cecilia; Nilsson, Kent W.; Hodgins, Sheilagh (Frontiers in Human Neuroscience, 2018)
The oxytocin receptor gene (OXTR) influences human behaviour. The G allele of OXTR rs53576 has been associated with both prosocial and maladaptive behaviours but few studies have taken account of environmental factors. The present study determined whether the association of childhood maltreatment with conduct problems was modified by OXTR rs53576 genotypes. In a general population sample of 1591 teenagers, conduct problems as well as maltreatment were measured by self-report. DNA was extracted from saliva samples. In males, there was a significant positive association between maltreatment and conduct problems independent of the genotype. In females, among G allele carriers, the level of conduct problems was significantly higher among those who had been maltreated as compared to those not maltreated. By contrast, among female AA carriers, conduct problems did not vary between those who were, and who were not, maltreated. The results indicate that OXTR rs53576 plays a role in antisocial behaviour in females such that the G allele confers vulnerability for antisocial behaviour if they experience maltreatment, whereas the A allele has a protective effect.